PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS XI MIA 1 SMAN 5 PEKANBARU - Putdawa, Khosicha Oktari; Heleni, Susda; Solfitri, Titi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research is classroom action research that aims to improve learning process and to increase the outcomes of mathematics learning of students by applying Problem Based Learning (PBL). The subjects of this research are the student of class XI MIA 1 SMAN 5 Pekanbaru at odd semester of academic years 2018/2019 wich total number of participant are 36 students, consists of 17 male students and 19 female students with heterogeneous academic achievement. This research have two cycles, each have four stages: planning, implementation, observation, and reflection. The research instrument consist of learning materials used include Syllabus, Lesson Plan and Student Work Sheets and instruments for collecting data are observation sheets and test of mathematics learning outcomes. Data analysis techniques in this study are descriptive narrative analysis and descriptive statistics analysis. From the analysis of observation sheets, it can be seen that there is improvement of learning process. The precentage and frequency of student who achieved minimum completeness criteria is increased from the basic score with percentage 47,22% (17 students) to cycle I with percentage 80,55% (29 students) and 88,89% (32 students) in cycle II. This research concludes that the implementation of PBL model improved the learning process and the student’s mathematics learning outcomes at class XI MIA 1 SMAN 5 Pekanbaru in the odd semester of the academic year 2018/2019Key Words: The outcomes of mathematics learning, Problem Based Learning,class action research